The status of Micronotus Hancock, 1902 species (Orthoptera: Tetrigidae) - Cadena-Castañeda, Oscar J.; Gonzalez, Gloria Raquel Dávila; Rodríguez, Martha Carolina Vásquez; Rodríguez, Diana Marcela Trujillo (Zootaxa, 2021)
In this contribution, we focus on the status of the genus Micronotus and its four species. After this revision, the genus only includes two of the four species, being synonymized Micronotus dubius n. syn. under M. quadriundulatus; includes within the genus M. andeanum n. comb. (transferred from the genus Tetrix) and confirming the status of M. asperulus. Micronotus is redescribed, including additional characters, and a key is provided to identify the three species considered as valid. Micronotus caudatus, is located in the new genus Danielatettix n. gen., by differing from and not fitting the diagnostic characteristics of Micronotus or another known genus of Tetriginae. The color variation of Danielatettix caudatus n. comb. is documented, and under this species its synonymized: Paratettix attenuata n. syn., P. hastata n. syn. and P. ignobilis n. syn. Finally, the distribution of the studied species and the taxonomic panorama of Tetriginae in the Neotropics are discussed.